SOIL ERODIBILITY ANALYSIS AND SOIL CONSERVATION TECHNIQUE IN THE BAWANG GAJAH SUB-WATERSHED, CENTRAL ACEH REGENCY: ANALISIS ERODIBILITAS TANAH DAN TEKNIK KONSERVASI TANAH DI SUB-DAS BAWANG GAJAH KABUPATEN ACEH TENGAH - Halim Akbar; Rini Fitri (ROCE : Jurnal Pertanian Terapan, 2025)
Soil erodibility is the ease with which soil is destroyed by the force of falling raindrops and/or surface runoff. This study aims to determine the soil erodibility value and soil conservation techniques in the Bawang Gajah sub-watershed. The method used in this study is a survey method consisting of preparation, preliminary survey, primary survey, data analysis, and presentation of results. Soil erodibility values were calculated using the Wischmeier and Smith equation. The results of the soil erodibility analysis showed that low soil erodibility values ranging from 0.27, 0.28, and 0.37 were found in Land Mapping Unit (LMU) 2, 4, 5, and 10, moderate soil erodibility values of 0.43 and 0.51 are found in LMU 6 and 7, high soil erodibility values of 0.61 and 0.64 are found in LMU 3 and 11. Very high soil erodibility values of 0.82 and 0.92 are observed in LMU 9 and 14, respectively. The conservation techniques that must be implemented on LMU 2, 4, 5, and 10 are planting ground cover vegetation, applying mulch, and practicing crop rotation. The conservation techniques to be applied to LMU 6 and 7 are a combination of agroforestry and contour terraces, along with the planting of vetiver grass. The soil conservation techniques that must be applied at LMU 3 and 11 are agroforestry and reforestation, as well as the construction of contour terraces for the rehabilitation of eroded areas, while at LMU 9 and 14, the soil conservation measures implemented are the construction of terraces equipped with diversion channels, terrace channels, and drainage channels.